Feeding ecology of the common wood pigeon (Columba palumbus) in a major European city - Álvaro Luna; Fernando Pomeda-Gutiérrez; Javier Galán Díaz (Royal Society Open Science, 2024)
Urban configuration and food availability influence birds’ foraging behaviour and constitute key factors for understanding how they exploit cities. Here, we conducted a field survey in the city of Madrid (Spain) from winter 2021 to autumn 2022 to understand how the common wood pigeon (Columba palumbus) exploits the food resources provided by urban parks and streets across different seasons. The proportion of observations away from parks increased during winter and spring, and the proportion of observations of wood pigeons eating on the ground was the greatest in summer. The common wood pigeon fed from 45 tree species, 60% of which were exotic ornamental species. Most tree species used as food sources coincided with those widely planted in parks, streets and avenues. The preferred trees varied throughout the year, with a greater incidence of exotic species in winter and spring. Our results show that the diversity of trees available in cities and the use of non-native plants with contrasting phenological patterns compared with the local flora are crucial elements in explaining the successful establishment of the common wood pigeon in the city.